Asian migrants' lived experience and acculturation to Western health care in rural Tasmania - Terry, D.; Ali, Mohammed; Le, Q. (Blackwell Publishing, 2011)
Objectives: The study was designed to explore the lived experience of Asian migrants' health care-seeking behaviour in Tasmania, to discern the acculturation process by which Asian migrants are enabled to use the health system and to identify strategies, which assist migrants to understand and use the health system better. Methods: Qualitative research was adopted. Semistructured interviews were conducted with 36 Asian migrants residing in North, South and North West Tasmania, which were recruited through purposive sampling. Results: Six main themes emerged from the interviews: the acculturation process, interactions with the health care system, access issues, culturally appropriate health care, positive health care in Tasmania and suggestions for improving health care. Conclusions: The findings indicated that Asian migrants' views affected their health care-seeking behaviours because of the lack of information, poor communication, limited access and choices in Tasmania. Interestingly, those married to local Tasmanians had the shortest trajectory to health system acculturation. The study recommended developing health and well-being for Asian migrants by increasing access to information regarding navigating the health system and improving access to and awareness of language services. In addition, ensuring adequate, appropriately written, culturally specific and congruent information should be available to assist migrants' transition into a new health care system. Lastly, greater cultural awareness within the health profession to meet the needs of culturally specific individuals and communities is required when they seek care.